«Ora diremo di Napoli». I traffici dell'area campana nei manuali di commercio - ORLANDI, ANGELA (Biblioteca di storia, 2012)
This work aims at filling some historiographical gaps concerning the economy and the commercial activities of Naples and its satellite ports in the decades around the turn of the fifteenth century using unusual and complicated sources such as Tuscan trading practices and Venetian tariffs. To the analysis of these materials the study of commercial letters sent to the Merchant of Prato by operators present in those areas was added. This addition offers two levels of interpretation, the first of which concerns the methodological aspects of the research. From the second, the one of results, a particularly articulated picture emerges in which the Neapolitan region appears as an attractive outlet market for woollen cloths and silk drapes manufactured in the cities of central-northern Italy and, at the same time, as an important supply market of some raw materials and many foodstuffs.